A new species of Zethus (Zethusculus) de Saussure (Hymenoptera, Vespidae, Eumeninae) from southern Brazil - Lopes,Rogério Botion (2015)
Zethus (Zethusculus) paschoali, a new species from Piraquara, Paraná, Brazil, is described and pictures comparing it to similar species are presented.